The Smear - Sharyl Attkisson (Harper, 2017)
Behind most major political stories in the modern era, there is an agenda; an effort by opposition researchers, spin doctors, and outside interests to destroy an idea or a person. The tactic they use is the Smear. Every day, Americans are influenced by the Smear without knowing it. Paid forces cleverly shape virtually every image you cross. Maybe you read that Donald Trump is a racist misogynist, or saw someone on the news mocking the Bernie Sanders campaign. The trick of the Smear is that it is often based on some shred of truth, but these media-driven hit pieces are designed to obscure the truth. Success hinges on the Smear artist’s ability to remain invisible; to make it seem as if their work is neither calculated nor scripted. It must appear to be precisely what it is not.